Konsep Tafsir, Ta`wil dan Hermeneutika: Pradigma Baru Menggeli Aspek Ahkam dalam Penafsiran Al-Qur`an - Muhamad Ali Mustofa Kamal (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2015)
The concept of interpretation (tafsir), exegesis (ta`wil) and hermeneutics as part of the art of understanding texts in the studi of the Qur`an gave birth to a new paradigm in undertsanding the Quur`anic text. Tafsir and ta`wil departure from Islamic tradition, while hermeneutic depart from the Wastern traditional. The development theory of inteerpretation and exegesis is essentially in order to development of hermeneutics as the theory of text interpretation is generally used as a tool to understand the text of holy Qur'an. This is no defferen from the interpretation (tafsir) and exegesis (ta`wil), it just that this hermeneutic is actually a development of the exegesis theory, as part of a philosophical theory, the theory of thinking to build a preu-understanding. The combination of the concept of interpreting and understanding the Qur`an wich `salihun li kulli zaman wa makan`.